2019
DOI: 10.3389/fphar.2019.00646
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopoietin Cn (HPPCn) Generates Protective Effects on Acute Liver Injury

Abstract: Objective: To observe the protective role of hapatopoietin Cn (HPPcn) on acute liver injury. Methods: Six hours after 10 mmol/L CCl 4 , 150 mmol/L ethanol, or 0.6 mmol/L H 2 O 2 treatment, SMMC7721 human hepatoma cells were incubated with 10, 100, or 200 ng/ml recombinant human HPPCn protein (rhHPPCn) for an additional 24 h. The cell survival rate was analyzed using the CCK-8 assay. The CCl 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, the content of MDA decreased significantly and the activities of SOD, GSH and CAT increased significantly in the liver tissue of mice in the ZDP groups, suggesting that ZDP has a certain antioxidant effect and can effectively improve the ability of cells to scavenge free radicals and reduce the damage to hepatocytes under free radical attack, which may be related to the antioxidant effect. These results were consistent with those of previous research (Li et al, 2019;Ren et al, 2019). IL-1β, IL-6, TNF-α and other inflammatory factors play an important role in the inflammatory process of acute tissue injury (Chalasani et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the content of MDA decreased significantly and the activities of SOD, GSH and CAT increased significantly in the liver tissue of mice in the ZDP groups, suggesting that ZDP has a certain antioxidant effect and can effectively improve the ability of cells to scavenge free radicals and reduce the damage to hepatocytes under free radical attack, which may be related to the antioxidant effect. These results were consistent with those of previous research (Li et al, 2019;Ren et al, 2019). IL-1β, IL-6, TNF-α and other inflammatory factors play an important role in the inflammatory process of acute tissue injury (Chalasani et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
“…Changes in body mass and liver index can reflect the degree of liver injury ( Li et al, 2019 ). As shown in Figure 3 , CCl 4 significantly reduced the body mass of mice ( p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Weight loss and liver index increase might indicate liver damage (Li et al, 2019). As observed in Figure 2, relative to the control group, in the model group, the body mass of rats was dramatically decreased (p < 0.05).…”
Section: Effects Of Hydroxysafflor Yellow a On Body Mass Wet Liver We...mentioning
confidence: 80%
“…Moreover, these ROS are capable of attacking fatty acids and causing peroxidation (Li et al, 2019). As the metabolic endproduct of lipid peroxides, MDA can aggravate cell membrane damage by destroying the function, structure, and metabolism of biofilms (Lixin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies reporting the key role of the oxidative stress in the hepatic injury, induced by CCl 4 . It has been found that chlorinated free radicals, formed via cytochrome P450 bio activation of CCl 4 , such as trichloromethyl (•CCl 3 ) and trichloromethyl peroxyl (•OOCCl 3 ) radicals, impair the hepatocytes, inducing morphological changes in the endoplasmic reticulum, Golgi apparatus, plasma membrane, and mitochondria of the targeted cells, leading to apoptosis (Li et al, 2019). Membrane disintegration of hepatocytes results in subsequent release of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and γ-glutamyltransferase (GGT) as well as decreased endogenous antioxidant defence system (Singh et al, 2008;Simeonova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%